Sweet home Chicago? : Mexican migration and the question of belonging and return - Bedorf, Franziska (Global studies (Bielefeld, Germany), 2018)
Based on long-term ethnographic fieldwork among aged Mexican migrants in Chicago, Franziska Bedorf investigates the phenomenon of return migration by tracing how people's intentions to go back change over time. Considering global labour mobility, she evaluates transformations of belonging and the wider economic, political, social and cultural frameworks that shape them. In front of the backdrop of debates on integration, transnationalism and belonging, the study explores why migrants keep and form attachments to and detachments from places, people and cultures.